2001
DOI: 10.1042/0264-6021:3590077
|View full text |Cite
|
Sign up to set email alerts
|

Role of connective tissue growth factor in the pathogenesis of diabetic nephropathy

Abstract: We characterized a rabbit polyclonal antibody raised against human recombinant connective tissue growth factor (CTGF). The antibody recognised a higher molecular mass form (approx. 56 kDa) of CTGF in mesangial cell lysates as well as the monomeric (36-38 kDa) and lower molecular mass forms (<30 kDa) reported previously. Immunohistochemistry detected CTGF protein in glomeruli of kidneys of non-obese diabetic mice 14 days after the onset of diabetes, and this was prominent by 70 days. CTGF protein is also presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 44 publications
6
122
0
1
Order By: Relevance
“…Although others have reported similar findings such as COLI and FN in rat renal fibroblasts (8) and FN and PAI-1 in human mesangial cells (25), to our knowledge, this is the first report to show an increase in TIMP-1 mRNA levels in murine renal fibroblasts in response to CTGF treatment. rhTGF-␀1 (1.0 ng/ml) increased the mRNA levels of ␣1COLI and FN-EIIIA in TFB that were co-cultured with mProx24 to a significantly greater degree than in TFB that were cultured alone, suggesting the involvement of profibrotic humoral factors secreted by the mProx24.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Although others have reported similar findings such as COLI and FN in rat renal fibroblasts (8) and FN and PAI-1 in human mesangial cells (25), to our knowledge, this is the first report to show an increase in TIMP-1 mRNA levels in murine renal fibroblasts in response to CTGF treatment. rhTGF-␀1 (1.0 ng/ml) increased the mRNA levels of ␣1COLI and FN-EIIIA in TFB that were co-cultured with mProx24 to a significantly greater degree than in TFB that were cultured alone, suggesting the involvement of profibrotic humoral factors secreted by the mProx24.…”
Section: Discussionsupporting
confidence: 47%
“…Their findings, coupled with ours, support the notion that CTGF acts as an important profibrotic mediator of TGF-␀'s effects in the renal tubulointerstitium while not eliminating the possibility that it plays a similar role in the glomerulus. In fact, a number of studies have shown that mesangial CTGF expression plays a role in the pathogenesis of glomerulosclerosis, especially in diabetic nephropathy (5,6,11,25,36). Because intravenously injected antisense ODN is not appreciably absorbed by glomerular cells, it cannot significantly block their expression of the target genes (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization was performed with cDNA probes labeled with [ 32 P]dCTP using the NonaPrimer kit from Appligene, Heidelberg, Germany. A cDNA specific for CTGF was kindly provided by N. Abdel-Wahab, London, UK (24). The blots were analyzed by phosphorimager or autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…CCN-2 bioactivity induces kidney fibroblast proliferation and ECM synthesis (Ito et al 1998), (Wahab et al 2001), (Twigg and Cooper 2004). Addition of recombinant CCN-2 to cultured mesangial cells increased the expression of ECM proteins including collagens and other matrix proteins present in DN (Murphy et al 1999).…”
Section: Ccn-2 As a Potential Key Mediator In Diabetic Nephropathymentioning
confidence: 99%